Successful Ultrasound-Guided Superficial Cervical Plexus Block Treatment for Head and Neck Pain with an Unusually Delayed Onset Following Ventriculoperitoneal Shunt: A Case Report - Ching-Yuan Hu; Ying-Zhen Huang; Sheng-Tzung Tsai; Po-Kai Wang (Medicina, 2023)
Background and Objectives: Ventriculoperitoneal (VP) shunt placement is the most common treatment for cerebrospinal fluid diversion. Head and neck pain occurring after a long period following VP shunt insertion is rarely reported. Here, we present a rare case of head and neck pain occurring 2 years after surgery due to irritation of the superficial cervical plexus by the VP shunt. Case Description: A 46-year-old female patient received VP shunt placement surgery. Two years after the surgery, she experienced a left temporal headache with neck pain on the left side, which extended to the left para-auricular and fascial region. Ultrasound (US) scanning revealed that the VP shunt passed within the superficial cervical fascia and through the left sternocleidomastoid muscle (SCM). Additionally, friction of the branches of the superficial cervical plexus and of the greater auricular and lesser occipital nerves caused by the VP shunt was found underneath the lateral border of the SCM. Subsequently, the blocking and hydro-release of the left superficial cervical plexus were performed. After four series of treatments, the patient’s head and neck pain vanished, and the frequency of the headaches was substantially reduced. The patient was regularly followed-up in the outpatient department of neurosurgery. Conclusions: Head and neck pain caused by the malpositioning of a VP shunt catheter with an unusually delayed onset is a rarely reported complication and could be easily neglected. Patients with head and neck pain following VP shunt insertion should be checked using US scanning to identify the potential origin of the pain and receive adequate treatments. Intraoperative US-guided tunnelling is suggested to avoid the malpositioning of the VP shunt catheter.